LAG3 (CD223) as a cancer immunotherapy target. Issue 1 (March 2017) - Andrews, Lawrence P.; Marciscano, Ariel E.; Drake, Charles G.; Vignali, Dario A. A.
Summary: Despite the impressive impact of CTLA4 and PD1‐PDL1‐targeted cancer immunotherapy, a large proportion of patients with many tumor types fail to respond. Consequently, the focus has shifted to targeting alternative inhibitory receptors (IRs) and suppressive mechanisms within the tumor microenvironment. Lymphocyte activation gene‐3 (LAG3) (CD223) is the third IR to be targeted in the clinic, consequently garnering considerable interest and scrutiny. LAG3 upregulation is required to control overt activation and prevent the onset of autoimmunity. However, persistent antigen exposure in the tumor microenvironment results in sustained LAG3 expression, contributing to a state of exhaustion manifest in impaired proliferation and cytokine production. The exact signaling mechanisms downstream of LAG3 and interplay with other IRs remain largely unknown. However, the striking synergy between LAG3 and PD1 observed in multiple settings, coupled with the contrasting intracellular cytoplasmic domain of LAG3 as compared with other IRs, highlights the potential uniqueness of LAG3. There are now four LAG3‐targeted therapies in the clinic with many more in preclinical development, emphasizing the broad interest in this IR. Given the translational relevance of LAG3 and the heightened interest in the impact of dual LAG3/PD1 targeting in the clinic, the outcome of these trials could serve as a nexus; significantly increasing or dampening enthusiasm for subsequent targets in the cancer immunotherapeutic pipeline.